Hepatitis C virus dynamics with viral load and T killer cells and hepatic damage monitoring without liver biopsies (2010)
This paper shows the possibility of predicting the status of an individual infected with the hepatitis C virus and monitoring the evolution of their viral load and liver damage, without the need for biopsies, by numerical estimation of the parameters of a Mathematical model of four populations (healthy and diseased hepatocytes, viral load and cytotoxic T cells), using measurements of viral load and cytotoxic T cells. It is also shown that the population of cytotoxic T cells does not significantly influence the estimation of the parameters, so it is sufficient to measure the viral load and the model reduced to three populations (healthy, diseased hepatocytes and viral load) to diagnose the disease evolution of an infected individual.